Indonesian story-telling ability based on image media of grade 1 students at MI Al-Mubarokah - Yusuf Safari; Sinta Ayu Nuresa (Mitra Palupi, 2022)
Background: This research is raised due to the problems of students who experience limitations in storytelling skills in Indonesian language lessons. This is due to the lack of concentration in the learning process because the learning methods and media used are less varied so that the ability to master the storytelling skills of students is low. Purpose: The purpose of this study was to determine the effectiveness of the use of image media on storytelling mastery in Indonesian language subjects for grade 1 students. Design and methods: This research was a quantitative experimental research, which was carried out at MI Al Mubarokah Cileungsi-Bogor. The form of experiment in this research is Post-test Only Control Group Design. The data collection technique that the author uses is in the form of observation and documentation. The subjects in this study were students of class 1 MI Al-Mubarokah, which consisted of 20 students who were divided into 2 groups, namely 10 students as the experimental class and 10 other students as the control group. Results: From the research results were analyzed using statistical analysis techniques. the p value is shown .000 < .05 that is indicated there is difference between the data mean of experiment and control class. Mean rank of experiment class is 27.05 while mean rank of control class is 13.95. it means the experiment class has higher mean than control. With this calculation the hypothesis can be concluded that picture media is improving the Indonesian story telling ability of the students. Then the application of image media is effective in improving storytelling skills in Indonesian subjects for class 1 students of MI Al Mubarokah Academic Year 2021/2022.